Pengaruh Konseling Obat Terhadap Pengetahuan dan Sikap Pasien Kolestrol di Rawat Jalan RS Advent Medan - br. Silalahi, Aancel; br. Sembiring, Novitaria; Hanjaya, Hanjaya; Razoki, Razoki; Neswita, Elfia (Dinasti Research, 2024)
Counseling is a practice that is needed by pharmacists because it provides significant benefits to patients. One of the important pharmaceutical services is counseling. Counseling, which comes from the word